Professional training of future primary school teachers in the context of Kazakh ethnopsychology and ethnopedagogy - Zhuzeyev, Serikkhan; Zhailauova, Manat (International Journal of Evaluation and Research in Education (IJERE), 2025)
Within the realm of primary education, the educational content and structure for the present youth generation are aligned with state regulations and rooted in the national values and traditions of the people. National education content should be integrated into primary school programs, with a focus on nurturing it through the ethnopsychological features and ethnopedagogical traditions of the nation. With that in mind, this study aims to enhance the ethnopedagogical and ethnopsychological professional qualifications of primary school teachers with focus on their ability to incorporate Kazakh national spiritual values and traditions in educational process. Research methodology includes theoretical instruments, consisting of analytical, and synthetic techniques, as well as pedagogical experiment, conducted via elective course “developmental and pedagogical psychology” among two groups of third-year university students from the department of primary education. To evaluate the effectiveness of the teacher training techniques, proposed in this study, we conducted and compared results of preliminary and final assessment of students’ professional competence. The research outcomes show the beneficial nature of training techniques and include an analysis of the content of the training carried out. These research findings can be applied in the further development of the fields of pedagogy and primary school methodology.